Vitamin D levels in young children with femur fractures at Charlotte Maxeke Johannesburg Academic Hospital - Pinkus, Daniella (My University, 2024)
Introduction: Fractures are common in children with healthy bones. However, the literature has shown that some of these fractures may be related to underlying bone pathology such as vitamin D deficiency. The aim of this study was to determine if there is vitamin D insufficiency or deficiency in children five years of age and younger with femur fractures at Charlotte Maxeke Johannesburg Academic Hospital. Methods: This study was a retrospective review of children with femur fractures admitted to the Charlotte Maxeke Johannesburg Academic Hospital paediatric orthopedic unit. The records of children admitted between 1 January 2017 and 31 December 2017 were retrieved. Demographic data were collected from clinical notes and electronic discharge summaries. Radiographs were assessed and blood results were retrieved. Results: Forty-five (n = 45) patients were enrolled for this study. The study sample comprised of 30 (66.7%) males with a mean age of 2.9 ± 1.3 (SD) years and 15 (33.3%) females with a mean age of 1.9 ± 1.1 (SD) years. The overall mean age for the sample population was 2.56 years (SD = 1.3, CI = 2.21 – 2.95). Of these patients, 42 (93.3%) were Black, 2 (4.5%) were White and 1 (2.2%) was Coloured. Falls accounted for the only mechanism of injury (n = 45). Spiral fractures accounted for the greatest proportion of fractures, followed by transverse fractures. Most patients (n = 34, 75.6%) came from inner city areas whilst the minority were from outer city areas (n = 11, 23.4%). Most children (68.9%) with femur fractures had low levels of serum 25-hydroxyvitamin D compared to children (31.1%) who had sufficient levels of serum 25-hydroxyvitamin D. Conclusion: This study showed that 68.9% of the children were vitamin D deficient or insufficient and 75.6 % were from inner city areas. This suggests that children aged five years and younger with femur fractures in our hospital may benefit from routine blood testing and vitamin D supplementation.
A research report submitted in partial fulfilment of the requirement for the degree of Master of Medicine (MMed) to the Faculty of Health Sciences, University of the Witwatersrand, School of Clinical Medicine, Johannesburg, 2023
Keywords: Femur fractures; Paediatric orthopedic unit; children's fractures